2009
DOI: 10.1177/0003319709333869
|View full text |Cite
|
Sign up to set email alerts
|

Is Inflammatory Bowel Disease a Risk Factor for Early Atherosclerosis?

Abstract: Inflammatory bowel disease patients have an increased risk of early atherosclerosis as shown by greater values of cIMT, carotid artery stiffness, Hyc, hsCRP, and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 35 publications
(51 reference statements)
6
92
0
6
Order By: Relevance
“…Interestingly, inflammatory bowel disease patients are reported to be at greater risk of developing atherosclerosis (37,38) and possibly, periodontal disease (39,40). Our study concurs with these observations: in response to the invading microbes, NOD2 loss of function in mice stimulates TLR2 signaling by up-regulation of TRAF6 and JNK3, leading to the production of NF-κB and resulting in the overexpression of serum cytokines, which play an important role in alveolar bone resorption in periodontitis and atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, inflammatory bowel disease patients are reported to be at greater risk of developing atherosclerosis (37,38) and possibly, periodontal disease (39,40). Our study concurs with these observations: in response to the invading microbes, NOD2 loss of function in mice stimulates TLR2 signaling by up-regulation of TRAF6 and JNK3, leading to the production of NF-κB and resulting in the overexpression of serum cytokines, which play an important role in alveolar bone resorption in periodontitis and atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…From a clinical point of view, the assessment of early atherosclerosis has been made by investigating surrogate markers such as the carotid artery intima-media thickness (IMT), flow-mediated vasodilatation of the brachial artery (FMD) and arterial stiffness by pulse wave velocity (PWV) [21][22][23][24][25][26][27][28][29][30]. The study by Aloi et coll, reported signs of endothelial dysfunction and early atherosclerosis even in children with IBD [27].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, aging, hypertension, diabetes, and hyperlipidemia have a major impact on the progression of atherosclerosis. In recent studies, there is an evolving evidence that IBD is an independent factor for development of atherosclerosis (7,8). Carotid intima-media thickness (CIMT) and pulse wave velocity (PWV) measurement methods were used to determine subclinical atherosclerosis in IBD (7)(8)(9) to reduced arterial elasticity and increased arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%